God’s perfection and human perfection: Mendelssohn’s account in the Evidenzschrift and its relation to Wolff’s philosophy - Lanzini Stobbe, Emanuel (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This paper aims to present the relationship between God’s perfection (God as the most perfect being) and the obligation for human perfection in Mendelssohn’s essay Abhandlung über die Evidenz in metaphysischen Wissenschaften, particularly with regard to his reception of Christian Wolff’s philosophy. In the Abhandlung, Mendelssohn seeks to investigate how much certainty there can be in philosophy – therefore including both natural theology and practical philosophy. Against this background, if we are to consider the interconnection between divine and human perfection, we must regard (a) Mendelssohn’s ontological proof of God as the most perfect being, as well as a teleological proof concerning the perfection of the world (in the third chapter of the Abhandlung); and (b) his account of the obligation human beings have to pursue our own perfection and that of others (in the fourth chapter), which is ultimately connected to the notion of the reflection of God’s perfections. In this paper, we shall firstly present Mendelssohn’s account of God as the most perfect being, and that of the perfection of the world; secondly consider his account of the law of nature and the obligation to pursue perfection; so that thirdly we may examine both notions against the background of Christian Wolff’s philosophy (particularly his natural theology and practical philosophy), to show that although Mendelssohn was substantially influenced by Wolff in both regards, he also introduced new nuances not present in Wolff’s account